2014
DOI: 10.1007/s00167-014-3483-6
|View full text |Cite
|
Sign up to set email alerts
|

Bone mineral density of the coracoid process decreases with age

Abstract: IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“… 4 , 13 , 22 , 25 Bone quality may have influenced load to failure because it has been shown that bone density decreases over time. 3 We tried to mitigate this limitation by using paired male shoulders so that both fixation techniques were applied to specimens of similar bone quality. In addition, failure of the suture button construct would probably occur at higher loads than seen in this study because most failures occurred at the clamp-muscle interface rather than at the glenoid.…”
Section: Discussionmentioning
confidence: 99%
“… 4 , 13 , 22 , 25 Bone quality may have influenced load to failure because it has been shown that bone density decreases over time. 3 We tried to mitigate this limitation by using paired male shoulders so that both fixation techniques were applied to specimens of similar bone quality. In addition, failure of the suture button construct would probably occur at higher loads than seen in this study because most failures occurred at the clamp-muscle interface rather than at the glenoid.…”
Section: Discussionmentioning
confidence: 99%
“…However, due to its mechanical characteristics in compression, this fixation method does not shield from a bone block fracture in case of decreased bone density, and we observed 1 intraoperative coracoid fracture in this series. 3 Properly positioning the bone graft on the margin of the glenoid cavity is one of the keys of Latarjet procedure. In a position too lateral, residual pain and long-term degenerative arthritis of glenohumeral joint was reported, whereas too medial, the failure rate with recurrent shoulder instability increased.…”
Section: Discussionmentioning
confidence: 99%
“…Lee et al proposed a number of potential theories which may have accounted for their case of stress fracture such as the repetitive forces on the coracoid during the different phases of the golf swing and the possibility of osteoporosis resulting in an insufficiency fracture. There is evidence that bone mineral density of the coracoid process decreases with age with suggestion of a predisposition to fracture from lower energy mechanisms [15]. Alt-hough the patient in our study was postmenopausal, there were no other predisposing factors that pointed towards an insufficiency fracture.…”
mentioning
confidence: 40%